Terminalia catappa leaf extracts inhibited metastasis of A2058 and A375 melanoma cells via downregulating p-Src and β-catenin pathway in vitro - Chin-Kuo Chang; Shu-Chen Chu; Jing-Yang Huang; Jing-Yang Huang; Pei-Ni Chen; Pei-Ni Chen; Yih-Shou Hsieh; Yih-Shou Hsieh (Frontiers Media S.A., 2022)
Background: Melanoma is a highly aggressive, lethal, and malignant cancer. Once diagnosed early, it can be easily removed and cured with satisfaction. Although many methods such as surgery, chemotherapy, radiotherapy, and immunotherapy have been used to treat this disease at an advanced stage, the outcomes are poor. Terminalia catappa leaves have been shown to have various biological benefits, including antitumor activity. The specific effects and molecular mechanisms of Terminalia catappa leaf in treating A2058 and A375 melanoma cells in vitro need to be clarified.Methods: The A2058 and A375 melanoma cancer cells were treated with Terminalia catappa leaf extracts, and then the effect of Terminalia catappa leaf extracts on migration and invasion was examined. The cell migration/invasion capacities of A2058 and A375 cells were investigated by a modified Boyden chamber assay. Zymography was used to clarify the activities of matrix metalloproteinases-2 and urinary type plasminogen activator. We performed a Western blot to verify the related expression of phospho-Src (Tyr416), phospho-Focal adhesion kinase (Tyr397), Vimentin, and β-catenin.Results: Modified Boyden chamber assays demonstrated that treatment of Terminalia catappa leaf extracts significantly inhibited A2058 and A375 cell migration/invasion capacities. In the zymography results, we showed that Terminalia catappa leaf extracts negatively modulated the activities of matrix metalloproteinases-2 and urinary type plasminogen activator. Western blot indicated that Terminalia catappa leaf extracts reduced the expression of phospho-Src (Tyr416), phospho-Focal adhesion kinase (Tyr397), Vimentin, and β-catenin.Conclusion:Terminalia catappa leaf extracts affected the antimetastasis of the A2058 and A375 melanoma cell lines by inhibiting the Focal adhesion kinase/Src interaction and Wingless-int1/β-catenin pathways in vitro. Terminalia catappa leaf extracts may serve as an effective chemopreventive agent against metastasis of melanoma cancer.